Perfect Meals with Pressure Cooking - Paula G. Harris-Swiatko; Karla P. Shelnutt; Amy Simonne; Sarah M. Ellis (EDIS)
Preparing great tasting, healthy meals can be a time-consuming task, but pressure cooking is a great way to prepare them in just minutes! Although they may seem old fashioned, pressure cookers are making a comeback because they can cook tough cuts of meats such as corned beef and stew beef to perfection and take far less time and energy than using standard boiling or steaming methods. This is a great option for today’s busy families who are trying to save both time and money! Pressure cooking is also a healthy cooking option as it maintains the natural flavor and nutrients of food. Delicious, healthy meals are just minutes away with this handy device! This 4-page fact sheet is a minor revision written by Paula G. Harris-Swiatko, Karla P. Shelnutt, Amy Simonne, and Sarah M. Ellis, and published by the Department of Family, Youth and Community Sciences, November 2019.